PRODUÇÃO DE GÁS HIDROGÊNIO UTILIZANDO GLICERINA E ELETRODOS METÁLICOS DE BAIXO CUSTO - Gallina, André Lazarin (2014)
Since the mid-2000s , Brazil has been gathering data from surveys conducted nationally and globally for the insertion of hydrogen gas in the Brazilian energy matrix, thus on 2010 a technical paper outlining the technology difficulties for producing hydrogen gas was published in Brazil and consequently used in research related to hydrogen. The main objective of this thesis is to produce electrochemically gas hydrogen from formic acid and glycerin utilizing low cost electrodes (304, 316, 254 stainless steel, copper, brass, carbon steel 1008, Armco iron and titanium alloy). The techniques employed were: cathodic potentiodynamic polarization, chronoamperometry, electrochemical impedance spectroscopy, optical microscopy and scanning electron microscopy, Raman spectroscopy, X- ray fluorescence, rotating disk electrode, scanning vibrating electrode technique. The studies showed the dependence of H2(g) evolution reaction with the surface treatment used , which resulted in the best polishing with emery SiC # 320. Hydrogen production also is related to the type of metal electrode used, especially 254 stainless steel that showed the best technical and economical results. The addition of benzotriazole 10-6 mol L-1 in the system containing 3 mol L-1 formic acid promoted the catalysis of hydrogen evolution reaction, due to partial adsorption of the same on the surface of metals. Assays employing glycerin in formic acid 3 mol L-1 showed the catalysis of the reaction of H2(g) and with the aid of an experimental design was possible to find the optimal concentration of glycerin, 0.1% (v/v). The results for Raman spectroscopy proved the adsorption of glycerin in the Fe2+ sites of the stainless steel electrode, confirming the competition between the adsorption of formic acid and glycerol in the system causing the catalysis of reaction.